Odpowiedzi

2010-01-08T22:08:13+01:00
4x+y=5
3x-2y=12

y=5-4x
3x-10+8x=12

y=5-4x
11x=22

y=5-4x
x=2

y=5-8
x=2

y=-3
x=2

b)
3x+4y=6
-x-2y=-4

3x+4y=6
x+2y=4

3x+4y=6
x=4-2y

12-6y+4y=6
x=4-24

12-6y+4y=6
x=4-2y

-2y=-6
x=4-2y

y=3
x=4-6

y-3
x=-2
9 4 9
Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-01-08T22:15:24+01:00
A)
4x+y=5
3x-2y=12
y=5-4x
3x-2(5-4x)=12
y=5-4x
3x+8x=12+10
y=5-4x
11x=22/:11
x=2
y=5-4x
y=3
x=2

b)
3x+4y=6
-x-2y=-4
-x=-4+2y
3(-4+2y)=6
-x=-4+2y
-12+6y=6
-x=-4+2y
6y=18/:6
y=3
-x=-4+6
y=3
-x=-2
22 4 22